Capabilities, Commitments and Effect on the Competitiveness of Small and Medium Enterprises (SME) in Medan - Yusrita Yusrita; Nur Augus Fahmi; Tri Kartika Yudha; Ismail Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Non-governmental group enterprises amounting to 152 business actors under the Medan Pemko building, and still need to increase the competitiveness of product quality caused by SMES have not had a high commitment in improving the business that must compete with the product A kind and low commitment business people to business in the building from scratch by not replacing the original product that they managed to have the competitiveness of the target company BDC. Which is the direction of this study to know the competitiveness of SME products with the method of survey and direct observation of SMES in the city of Medan consist of 21 districts and what factors cause the ability to compete low SME actors in the city of Medan By linking to SMB capability variables and commitment to its business. Analysis of the techniques used by using some linear regression analysis result test results obtained. Ability to influence but if the SME's commitment is improved, it will make the competitiveness of SMES competing with other similar businesses can increase.